Function of income and education performance in Mexico - Barceinas, Fernando (Estudios Económicos de El Colegio de México, 1999)
This article analyzes the relationship between income and education in Mexico by calculating a rate of return for education. The data used was obtained from the Household Budget Survey of 1992, EMGH. Various methods (direct, a mincerian income function, and "elaborate" or discount rate) and formal functions (using years of education, and controlling or not for hours worked) are used. The results show the usefulness of controlling for hours worked, and that the best fit is obtained when using the non-restricted "elaborate" method. Some of the most important and specific results are the higher rate of return of high school studies, and the higher rates of return to schooling for men with primary and university studies.